Reduced graphene oxide–GelMA–PCL hybrid nanofibers for peripheral nerve regeneration. Issue 46 (2nd November 2020) - Fang, Xingxing; Guo, Haichang; Zhang, Wei; Fang, Haoming; Li, Qicheng; Bai, Shulin; Zhang, Peixun
Abstract : Graphene oxide is currently used in peripheral nerve engineering but has certain limitations, such as cytotoxicity and lack of electrical conductivity, both of which are crucial in regulating nerve-associated cell behaviors. Abstract : Graphene oxide is currently used in peripheral nerve engineering but has certain limitations, such as cytotoxicity and lack of electrical conductivity, both of which are crucial in regulating nerve-associated cell behaviors. In this work, we engineered reduced graphene oxide–GelMA–PCL nanofiber nerve guidance conduits via electrospinning. rGO incorporated into the GelMA/PCL matrix significantly enhanced the electrical conductivity and biocompatibility of the hybrid materials. In addition, hybrid nanofibers with low concentrations of rGO (0.25 and 0.5 wt%) could significantly improve the proliferation of Schwann cells (RSC96). More importantly, rGO/GelMA/PCL hybrid nanofibers could activate the epithelial–mesenchymal transition (EMT)-related gene expression of Schwann cells (RSC96). From the in vivo study, it was observed that rGO/GelMA/PCL nerve guidance conduits could promote both sensory/motor nerve regeneration and functional recovery in rats. Our composite strategy of combining rGO within a biocompatible nanofiber scaffold is simple but effective in improving tissue engineering outcomes. The rGO/GelMA/PCL hybrid nanofibers have great potential in peripheral nerve tissue engineering. They will also provide an experimental basis for the development of further electrical stimulation in peripheral nerve regeneration.